A sheath rubber material for energy storage battery connecting cable and preparation method thereof

By using polyurethane rubber and styrene butadiene rubber in the sheath layer material of the energy storage battery connection cable, combining graphene and composite halogen-free flame retardant system, it has formed high and low temperature resistant, flame retardant and flexible rubber, which has solved the problem of current There are insufficient materials in the high temperature range and structural stability, which meets the high performance needs of energy storage battery connection cables.

CN114874606BActive Publication Date: 2024-12-13TBEA DEYANG CABLE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210696964.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2024-12-13
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

The sheathing material of the existing energy storage battery connection cable cannot meet the temperature resistance requirements of -40℃~125℃, and is suitable for cables with smaller specifications during the production process. The structural stability is poor and the high flexibility cannot be met. Ideal technical requirements such as ultraviolet resistance.

Method used

Adopt a rubber system mainly composed of polyurethane rubber and styrene butadiene rubber, add ethylene propylene rubber-graphene mixture, nitrile rubber, sodium silicate binder, liquid silicone rubber, hexamethylcyclotrisilazane, and organosilane Coupling agent, nanoboronitride powder and composite halogen-free flame retardant system form a sheathing material that is resistant to high and low temperatures, flame retardant and flexible through multiple mixing.

Benefits of technology

The high and low temperature resistance of the rubber has been improved to -40℃~150℃, the tensile strength is ≥12MPa, the elongation rate of break is ≥300%, and the aging coefficient of 150℃ is ≤±30%, which fully meets the connection cable of the energy storage battery. Ideal technical requirements for sheathing layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003703016510000021
    Figure BDA0003703016510000021
  • Figure BDA0003703016510000031
    Figure BDA0003703016510000031
  • Figure BDA0003703016510000041
    Figure BDA0003703016510000041
Patent Text Reader

Abstract

The present invention discloses a sheath rubber compound for energy storage battery connection cable and a preparation method thereof. The raw material ratio of the sheath rubber compound is: 35-50 parts of polyurethane rubber, 15-25 parts of styrene-butadiene rubber, 60-80 parts of EPDM-graphene mixture, 20-30 parts of nitrile rubber, 10-20 parts of sodium silicate adhesive, 4-8 parts of hexamethylcyclotrisilazane, 5-10 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 10-15 parts of liquid silicone rubber, 1-1.5 parts of organic silane coupling agent, 0.5-1 parts of cycloalkyl rubber oil, 10-15 parts of nano boron nitride powder, 2-4 parts of granular acetylene conductive carbon black, 25-35 parts of composite halogen-free flame retardant system, 15-30 parts of reinforcing agent, 3-6 parts of antioxidant, 10-15 parts of low-temperature plasticizer, and 3-5 parts of vulcanization system additive. It has excellent resistance to battery acid, strong alkali, halogen-free flame retardancy, mineral oil resistance, high and low temperature resistance, thermal life, and UV resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The invention relates to a sheath material for cable molding, in particular to a sheath rubber compound for molding a connecting cable of an energy storage battery, and a preparation method of the sheath rubber compound. Background Art

[0002] As a renewable energy conversion device, energy storage equipment is related to energy transformation and energy structure adjustment, and has been developing strongly in recent years. Common energy storage equipment includes solar power generation equipment, wind power generation equipment, etc. In energy storage equipment, there is a key component - energy storage battery. The common energy storage battery is lead-acid battery, which is a typical electrochemical energy storage system.

[0003] In the structure of energy storage batteries, connecting cables are an important part of electrochemical energy storage systems. Specifically, in the structure of energy storage batteries, connecting cables are mainly used in working conditions such as between DC side battery modules, between battery clusters, between battery clusters and junction boxes, or between battery clusters and energy storage inverters in power storage systems. They require long-term high-power charging and discharging, as well as potential risks of contact with battery acid. Therefore, the connecting cables used for energy storage batteries should preferably have excellent thermal life, resistance to battery acid, resistance to strong alkali, halogen-free flame retardancy and other properties. In addition, in order to meet the application conditions such as open air and mobile environments, the connecting cables used for energy storage batteries should preferably also have excellent resistance to mineral oil, high and low temperature resistance (temperature range of -40℃~125℃), salt spray resistance, and UV resistance. This also requires that the material used to form the sheath layer of the energy storage battery connection cable should preferably have excellent thermal life, resistance to battery acid, resistance to strong alkali, halogen-free flame retardancy, resistance to mineral oil, resistance to high and low temperatures (temperature range is -40℃~125℃), resistance to salt spray, and resistance to ultraviolet rays.

[0004] At present, the materials used for forming the sheath layer of the energy storage battery connection cable are mainly acid- and alkali-resistant PVC materials, low-smoke halogen-free cross-linked polyolefin materials, chlorinated polyethylene rubber materials, etc. Among them, the acid- and alkali-resistant PVC materials, due to the presence of chlorine elements, will produce a large amount of halogen gas during the combustion process, which is easy to cause gas poisoning in the narrow and confined space of the energy storage module. The flame retardancy, environmental protection and safety are poor, and it cannot meet the ideal technical requirements of halogen-free flame retardancy of energy storage battery connection cables. Although the low-smoke halogen-free cross-linked polyolefin materials have good flame retardancy and environmental protection properties, due to the addition of a large amount of aluminum hydroxide and magnesium hydroxide as halogen-free flame retardants and a large amount of ammonium octamolybdate as a smoke suppressant in the polyolefin materials, its mechanical properties and weather resistance are deteriorated, and it cannot meet the ideal technical requirements of high flexibility and UV resistance of energy storage battery connection cables. Although the chlorinated polyethylene rubber material has good flexibility, its oil resistance and acid- and alkali resistance are poor, and it contains halogens, which also cannot meet the ideal technical requirements of energy storage battery connection cables. It can be seen that the mainstream materials currently used for the sheath layer of the formed energy storage battery connection cable can more or less fail to meet the ideal technical requirements of the application conditions of the energy storage battery connection cable.

[0005] Chinese patent literature discloses a technology named "A radiation-crosslinked silicone rubber-based energy storage cable material and its preparation method" (publication number CN 112430367 A, publication date March 2, 2021). The technology discloses a material used as the sheath layer of a molded energy storage battery connection cable, which has good solvent resistance, oil resistance, battery acid resistance, alkali resistance, flame retardancy, thermal life, mechanical properties and other properties. However, the high and low temperature resistance of this technology is poor, that is, it cannot meet the ideal technical requirements that the sheath layer of the energy storage battery connection cable should be resistant to high and low temperatures of -40°C to 125°C. In addition, the material system of this technology is formulated by radiation cross-linking process. The radiation cross-linking process is only applicable to cables with smaller specifications in the production process of connecting cables, and the structural stability of the cables produced is poor. Summary of the invention

[0006] The technical purpose of the present invention is to provide a sheath rubber compound for energy storage battery connection cable with excellent thermal life, resistance to battery acid, resistance to strong alkali, halogen-free flame retardancy, resistance to mineral oil, resistance to high and low temperatures (temperature range of -40°C to 150°C), resistance to salt spray, resistance to ultraviolet rays, and the like, in view of the particularity of the application conditions of the above-mentioned energy storage battery connection cable and the deficiencies of the prior art, and a preparation method of the sheath rubber compound.

[0007] The technical purpose of the present invention is achieved by the following technical solution: a sheath rubber compound for energy storage battery connection cable, wherein the raw material ratio of the sheath rubber compound is calculated according to the following weight components:

[0008]

[0009]

[0010] The rubber system of the above technical measures is mainly composed of polyurethane rubber and styrene-butadiene rubber, supplemented by EPDM rubber-graphene mixture, which cooperate and match each other to form a base material that is wear-resistant, heat-resistant, oil-resistant, aging-resistant, and soft. In the base material, by adding synergistic and compatible nitrile rubber, the battery acid and strong alkali resistance of the rubber are effectively improved; by adding synergistic and compatible maleic anhydride grafted ethylene vinyl acetate copolymer, it is beneficial to the molecular grafting between rubbers, thereby effectively improving the performance of the rubber; by adding synergistic and compatible sodium silicate adhesive, the bonding effect of the sodium silicate adhesive is utilized to make the graphene molecules in the EPDM rubber-graphene mixture more easily and reliably attached to the rubber; by adding synergistic and compatible liquid silicone rubber, the heat resistance of the rubber is improved. The temperature of the rubber compound is effectively raised to 150℃; by adding synergistic and compatible low-temperature plasticizers, the low-temperature resistance of the rubber compound is effectively reduced to -40℃; by adding synergistic and compatible hexamethylcyclotrisilazane, the compatibility of liquid silicone rubber is effectively enhanced, thereby effectively enhancing the high and low temperature resistance of the rubber compound, so that the temperature resistance range of the rubber compound reaches -40℃~150℃, which is far better than the current ideal technical requirements for the temperature resistance range of the sheath layer material of the molded energy storage battery connection cable (i.e. -40℃~125℃); by adding synergistic and compatible organic silane coupling agents, The whole rubber compound is modified as a whole, thereby improving the comprehensive properties of the whole rubber compound such as mechanical properties, electrical insulation properties and anti-aging properties; by adding synergistic and compatible cycloalkyl rubber oil, it effectively assists the mixing and dispersion of fillers in the whole rubber compound, thereby reducing the viscosity of the whole rubber compound and the mixing energy consumption, which is beneficial to adjust the physical and mechanical properties of the vulcanized rubber; by adding synergistic and compatible composite halogen-free flame retardant system, the rubber compound has excellent flame retardant effect, even in the combustion process, it will not release harmful halogen gases, etc., it has good environmental protection, and effectively reduces the single flame retardant Large-scale use will not have an adverse effect on the mechanical properties of the rubber; by adding synergistic and compatible nano boron nitride powder, the overall high temperature resistance and high flame retardancy of the entire rubber are effectively enhanced, and it is also beneficial to improve the insulation performance of the entire rubber; by adding synergistic and compatible granular acetylene conductive carbon black, the weather resistance and heat aging performance of the rubber are effectively enhanced. Compared with other carbon blacks, it has the characteristics of light weight, small specific gravity, large specific surface area, strong adsorption, stable chemical properties, good surface activity, etc., and has better fluidity and dispersibility when mixed in the rubber.

[0011] As one of the preferred solutions, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0012]

[0013] The above technical measures prepare an EPDM-graphene mixture, with EPDM as the main material, supplemented with a small amount of graphene powder, graphene dispersant, nano zinc oxide, and sodium silicate adhesive, through melt dispersion blending, so that the graphene powder is excellently dispersed on the molecular chain of EPDM, effectively improving the tensile strength and elongation at break of EPDM, significantly improving the mechanical properties of the material, and reliably cooperating and matching with polyurethane rubber and styrene-butadiene rubber.

[0014] As one of the preferred solutions, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0015]

[0016] The above technical measures use phosphorus flame retardants (i.e. DOPO intermediates), metal hydroxides (i.e. aluminum hydroxide and magnesium hydroxide), expandable graphite, etc., and mix them into an excellent halogen-free flame retardant system. In this system, expandable graphite is used in combination with phosphorus flame retardants and metal hydroxides to produce a synergistic effect, achieve an enhanced flame retardant effect, and effectively reduce the adverse effects of a large amount of single flame retardant on the mechanical properties of the entire rubber compound, which is environmentally friendly and flame retardant.

[0017] As one of the preferred solutions, the grafting rate of the maleic anhydride grafted ethylene vinyl acetate copolymer is 1.5-2.0%, and the incorporation index is 3-6 g / 10 min. This technical measure is aimed at the grafting copolymerization between rubber molecules such as polyurethane rubber and styrene-butadiene rubber in the rubber system, and has a higher grafting efficiency and a more excellent improvement on the rubber performance.

[0018] A method for preparing the above-mentioned sheath rubber material for energy storage battery connection cable, the preparation method comprising the following process steps:

[0019] Step 1. Prepare an EPDM rubber-graphene mixture for later use;

[0020] Prepare a composite halogen-free flame retardant system for standby use;

[0021] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0022] The plasticizing time is 50 to 60 minutes to obtain a mixed rubber base material;

[0023] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0024] The internal mixer is heated to 90-100°C and the mixing time is 40-45 minutes to obtain a mixed rubber material 1;

[0025] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0026] The mixing time is 20 to 30 minutes to obtain mixed rubber material 2;

[0027] Step 5. Filter the mixed rubber material 2 in a filter;

[0028] Step 6. The filtered rubber material is sheeted on a calender and left to stand for at least 24 hours after cooling;

[0029] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0030] The mixing time is 25 to 30 minutes to obtain mixed rubber material 3;

[0031] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0032] The mixing time is 25 to 30 minutes to obtain mixed rubber material 4;

[0033] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0034] The above preparation method is to prepare the sheath rubber compound for cable production by mixing the components of the above rubber compound system for many times. The rubber compound has the following main properties after laboratory testing: tensile strength ≥12MPa, elongation at break ≥300%, aging coefficient of hot air at 150℃×168h (≤±30%, ≤±30%), aging coefficient of 150℃×72h in 902# oil (mineral oil) (≤±30%, ≤±30%), low-temperature tensile strength at -40℃ is ≥60%, minimum tear strength (8N / mm), and oxygen index is greater than 36. It can be seen that the rubber compound has excellent battery acid resistance, strong alkali resistance, halogen-free flame retardant, mineral oil resistance, high and low temperature resistance (temperature resistance range is -40℃~150℃), high heat life, ultraviolet resistance and other properties, and fully meets the ideal technical requirements of the sheath layer of the energy storage battery connection cable.

[0035] As one of the preferred solutions, the method for preparing the EPDM rubber-graphene mixture in step 1 specifically includes the following process steps:

[0036] Step ①. Dispersing graphene powder in sodium silicate binder;

[0037] An ultrasonic rod is used for ultrasonic mixing, the ultrasonic frequency is 2500-3000 Hz, and the ultrasonic vibration time is 20-30 minutes to obtain a graphene adhesive;

[0038] Step ②. Preheat the internal mixer to 115-120°C;

[0039] Adding EPDM rubber, graphene dispersant, nano zinc oxide and graphene binder into an internal mixer;

[0040] The rotation speed of the internal mixer is adjusted to 110-120 rpm, the heating temperature of the internal mixer is adjusted to 80-90° C., the materials in the internal mixer are subjected to high-speed shear dispersion for at least 20 minutes, and an EPDM rubber-graphene mixture is obtained.

[0041] The above method disperses the graphene powder under high-speed shearing, and utilizes the discrete effect of nano zinc oxide to disperse the graphene powder on the molecular chain of the high-temperature molten EPDM rubber. At the same time, through the bonding effect of the sodium silicate adhesive, the adhesion of the graphene molecules is effectively enhanced, thereby improving the tensile strength and elongation at break of the EPDM rubber, and significantly improving the mechanical properties of the material.

[0042] As one of the preferred solutions, the method for preparing the composite halogen-free flame retardant system in step 1 specifically includes the following process steps:

[0043] Step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite and cycloalkyl rubber oil into a mixer;

[0044] Mixing is performed in an alternating manner of forward stirring and reverse stirring, the stirring rate is 400-600 r / min, the alternating interval between forward and reverse stirring is 0.5-2 min, and the total stirring time is 10-20 min;

[0045] Step ②. Heat the mixer to 55-65°C and keep warm, continue stirring for 15-30 minutes to obtain a composite halogen-free flame retardant mixture.

[0046] The above method fully mixes the selected flame retardant components so that the components are effectively compounded into a whole, producing a flame retardant synergistic effect, thereby forming a halogen-free flame retardant system with excellent performance, achieving an enhanced flame retardant effect, which is far better than the flame retardant effect of a single flame retardant, and effectively reduces the adverse effects of a single flame retardant on the mechanical properties of the rubber system caused by the large amount of addition.

[0047] As one of the preferred solutions, the filter in step 5 has two layers of filter screens, the first layer of filter screen is 60 mesh, and the second layer of filter screen is 80 mesh;

[0048] The second mixed rubber material is filtered at least twice before and after in the filter.

[0049] This technical measure can effectively remove impurities in the mixed rubber and reliably improve the quality of the produced rubber.

[0050] The beneficial technical effect of the present invention is that the above technical measures are aimed at the particularity of the application conditions of the energy storage battery connection cable, and the obtained rubber material has the following main properties after laboratory testing:

[0051] Tensile strength ≥12MPa;

[0052] Elongation at break ≥ 300%;

[0053] 150℃×168h hot air aging coefficient (≤±30%, ≤±30%);

[0054] Aging coefficient at 150℃×72h in 902# oil (mineral oil) (≤±30%, ≤±30%);

[0055] Low temperature stretch at -40°C is ≥60%;

[0056] Minimum tear strength (8N / mm);

[0057] Oxygen index greater than 36;

[0058] It has excellent resistance to battery acid, strong alkali, halogen-free flame retardancy, mineral oil resistance, high and low temperature resistance (temperature range is -40℃~150℃), high thermal life, UV resistance and other properties, and can fully meet the ideal technical requirements of the sheath layer of energy storage battery connection cable.

[0059] Compared with the technology of publication number CN 112430367 A, the present invention not only has a higher limit value of high and low temperature resistance, but also is prepared by a vulcanization cross-linking process, which can be applied to cables of different specifications, large and small, during the production process of connecting cables, and the produced cables have good structural stability. DETAILED DESCRIPTION

[0060] The present invention relates to a sheath material for cable molding, specifically a sheath rubber compound for molding a connecting cable of an energy storage battery, and a preparation method of the sheath rubber compound. The technical solution of the present invention is clearly and detailedly described below with multiple embodiments.

[0061] Example 1

[0062] The raw material ratio of the sheath rubber system of the present invention is calculated according to the following components by weight:

[0063] 40 parts of polyurethane rubber, 20 parts of styrene-butadiene rubber, 65 parts of EPDM-graphene mixture, 23 parts of nitrile rubber, 18 parts of sodium silicate adhesive, 6 parts of hexamethylcyclotrisilazane, 7 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 10 parts of liquid silicone rubber, 1.2 parts of organic silane coupling agent, 0.6 parts of cycloalkyl rubber oil, 10 parts of nano boron nitride powder, 3 parts of granular acetylene conductive carbon black, 27 parts of composite halogen-free flame retardant system, 20 parts of reinforcing agent, 3 parts of antioxidant, 10 parts of low-temperature plasticizer, and 3 parts of vulcanization system additives.

[0064] In the above-mentioned rubber system, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0065] 65 parts of EPDM rubber, 2 parts of graphene powder, 0.2 parts of graphene dispersant, 1.3 parts of nano zinc oxide, and 11 parts of sodium silicate adhesive.

[0066] In the above-mentioned rubber system, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0067] 11 parts of DOPO intermediate, 6 parts of aluminum hydroxide, 7 parts of magnesium hydroxide, 3 parts of expandable graphite, and 12 parts of cycloalkyl rubber oil.

[0068] In the above-mentioned rubber system, the grafting rate of maleic anhydride grafted ethylene vinyl acetate copolymer is in the range of 1.5-2.0%, and the incorporation index is in the range of 3-6 g / 10 min.

[0069] The preparation method of the above-mentioned rubber system comprises the following process steps:

[0070] Step 1. Prepare an EPDM-graphene mixture, and the specific preparation method includes the following detailed process steps: Step ①. Disperse graphene powder in sodium silicate adhesive; use an ultrasonic rod for ultrasonic mixing, the ultrasonic frequency is about 2500HZ, and the ultrasonic vibration time is about 28min, to obtain a graphene adhesive; Step ②. Preheat the internal mixer to about 115°C; add EPDM, graphene dispersant, nano zinc oxide and graphene adhesive into the internal mixer; adjust the speed of the internal mixer to about 115 rpm, adjust the heating temperature of the internal mixer to about 80°C, and perform high-speed shear dispersion on the materials in the internal mixer for about 21min to obtain an EPDM-graphene mixture;

[0071] The obtained EPDM-graphene mixture is used for later use;

[0072] The composite halogen-free flame retardant system is prepared. The specific preparation method includes the following detailed process steps: step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite, and cycloalkyl rubber oil into a mixer; mix them in an alternating manner of forward stirring and reverse stirring, the stirring rate is about 420r / min, the alternating interval time of forward and reverse stirring is about 1min, and the total stirring time is about 15min; step ②. Heat the mixer to about 60°C and keep it warm, and continue stirring for about 15min to obtain a composite halogen-free flame retardant mixture;

[0073] The obtained composite halogen-free flame retardant mixture is used for standby use;

[0074] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0075] The plasticizing time is about 55 minutes to obtain a mixed rubber base;

[0076] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0077] The internal mixer was heated to about 90°C and the mixing time was about 45 minutes to obtain a mixed rubber material 1;

[0078] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0079] The mixing time is about 26 minutes, and the mixed rubber material 2 is obtained;

[0080] Step 5. Filter the mixed rubber material 2 in a filter, wherein the filter has a front layer and a rear layer of filter screens, the first layer of filter screen is about 60 meshes, and the second layer of filter screen is about 80 meshes;

[0081] The mixed rubber material 2 is filtered twice before and after in the filter to remove impurities;

[0082] Step 6. The filtered rubber material is sheeted on a calender and left to stand for about 25 hours after cooling;

[0083] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0084] The mixing time is about 26 minutes, and the mixed rubber material 3 is obtained;

[0085] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0086] The mixing time is 25 min, and the mixed rubber material 4 is obtained;

[0087] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0088] Example 2

[0089] The raw material ratio of the sheath rubber system of the present invention is calculated according to the following components by weight:

[0090] 36 parts of polyurethane rubber, 16 parts of styrene-butadiene rubber, 70 parts of EPDM-graphene mixture, 23 parts of nitrile rubber, 15 parts of sodium silicate adhesive, 7 parts of hexamethylcyclotrisilazane, 9 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 12 parts of liquid silicone rubber, 1.2 parts of organic silane coupling agent, 0.8 parts of cycloalkyl rubber oil, 13 parts of nano boron nitride powder, 2 parts of granular acetylene conductive carbon black, 32 parts of composite halogen-free flame retardant system, 16 parts of reinforcing agent, 4 parts of antioxidant, 12 parts of low-temperature plasticizer, and 3 parts of vulcanization system additives.

[0091] In the above-mentioned rubber system, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0092] 70 parts of EPDM rubber, 3 parts of graphene powder, 0.3 parts of graphene dispersant, 1.6 parts of nano zinc oxide, and 14 parts of sodium silicate adhesive.

[0093] In the above-mentioned rubber system, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0094] 13 parts of DOPO intermediate, 6 parts of aluminum hydroxide, 6 parts of magnesium hydroxide, 4 parts of expandable graphite, and 11 parts of cycloalkyl rubber oil.

[0095] In the above-mentioned rubber system, the grafting rate of maleic anhydride grafted ethylene vinyl acetate copolymer is in the range of 1.5-2.0%, and the incorporation index is in the range of 3-6 g / 10 min.

[0096] The preparation method of the above-mentioned rubber system comprises the following process steps:

[0097] Step 1. Prepare an EPDM-graphene mixture, and the specific preparation method includes the following detailed process steps: Step ①. Disperse graphene powder in sodium silicate adhesive; use an ultrasonic rod for ultrasonic mixing, the ultrasonic frequency is about 2800HZ, and the ultrasonic vibration time is about 25min, to obtain a graphene adhesive; Step ②. Preheat the internal mixer to about 116°C; add EPDM, graphene dispersant, nano zinc oxide and graphene adhesive into the internal mixer; adjust the speed of the internal mixer to about 112 rpm, adjust the heating temperature of the internal mixer to about 83°C, and perform high-speed shear dispersion on the materials in the internal mixer for about 20min to obtain an EPDM-graphene mixture;

[0098] The obtained EPDM-graphene mixture is used for later use;

[0099] The composite halogen-free flame retardant system is prepared. The specific preparation method includes the following detailed process steps: step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite, and cycloalkyl rubber oil into a mixer; mix them in an alternating manner of forward stirring and reverse stirring, the stirring rate is about 490r / min, the alternating interval time of forward and reverse stirring is about 0.8min, and the total stirring time is about 13min; step ②. Heat the mixer to about 58°C and keep it warm, and continue stirring for about 22min to obtain a composite halogen-free flame retardant mixture;

[0100] The obtained composite halogen-free flame retardant mixture is used for standby use;

[0101] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0102] The plasticizing time is about 52 minutes to obtain a mixed rubber base;

[0103] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0104] The internal mixer was heated to about 93°C and the mixing time was about 43 minutes to obtain a mixed rubber material 1;

[0105] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0106] The mixing time is about 22 minutes, and the mixed rubber material 2 is obtained;

[0107] Step 5. Filter the mixed rubber material 2 in a filter, wherein the filter has a front layer and a rear layer of filter screens, the first layer of filter screen is about 60 meshes, and the second layer of filter screen is about 80 meshes;

[0108] The mixed rubber material 2 is filtered twice before and after in the filter to remove impurities;

[0109] Step 6. The filtered rubber material is sheeted on a calender and left to stand for about 24 hours after cooling;

[0110] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0111] The mixing time was about 27 minutes, and the mixed rubber material 3 was obtained;

[0112] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0113] The mixing time was about 27 minutes, and the mixed rubber material 4 was obtained;

[0114] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0115] Example 3

[0116] The raw material ratio of the sheath rubber system of the present invention is calculated according to the following components by weight:

[0117] 45 parts of polyurethane rubber, 18 parts of styrene-butadiene rubber, 78 parts of EPDM-graphene mixture, 21 parts of nitrile rubber, 13 parts of sodium silicate adhesive, 4 parts of hexamethylcyclotrisilazane, 6 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 12 parts of liquid silicone rubber, 1 part of organic silane coupling agent, 0.7 parts of cycloalkyl rubber oil, 12 parts of nano boron nitride powder, 3 parts of granular acetylene conductive carbon black, 30 parts of composite halogen-free flame retardant system, 20 parts of reinforcing agent, 4 parts of antioxidant, 13 parts of low-temperature plasticizer, and 4 parts of vulcanization system additives.

[0118] In the above-mentioned rubber system, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0119] 72 parts of EPDM rubber, 3 parts of graphene powder, 0.3 parts of graphene dispersant, 2.2 parts of nano zinc oxide, and 13 parts of sodium silicate adhesive.

[0120] In the above-mentioned rubber system, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0121] 13 parts of DOPO intermediate, 7 parts of aluminum hydroxide, 8 parts of magnesium hydroxide, 4 parts of expandable graphite, and 13 parts of cycloalkyl rubber oil.

[0122] In the above-mentioned rubber system, the grafting rate of maleic anhydride grafted ethylene vinyl acetate copolymer is in the range of 1.5-2.0%, and the incorporation index is in the range of 3-6 g / 10 min.

[0123] The preparation method of the above-mentioned rubber system comprises the following process steps:

[0124] Step 1. Prepare an EPDM-graphene mixture, and the specific preparation method includes the following detailed process steps: Step ①. Disperse graphene powder in sodium silicate adhesive; use an ultrasonic rod for ultrasonic mixing, the ultrasonic frequency is about 2950HZ, and the ultrasonic vibration time is about 30min, to obtain a graphene adhesive; Step ②. Preheat the internal mixer to about 115°C; add EPDM, graphene dispersant, nano zinc oxide and graphene adhesive into the internal mixer; adjust the speed of the internal mixer to about 120 rpm, adjust the heating temperature of the internal mixer to about 90°C, and perform high-speed shear dispersion on the materials in the internal mixer for about 22min to obtain an EPDM-graphene mixture;

[0125] The obtained EPDM-graphene mixture is used for later use;

[0126] The composite halogen-free flame retardant system is prepared. The specific preparation method includes the following detailed process steps: step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite, and cycloalkyl rubber oil into a mixer; mix them in an alternating manner of forward stirring and reverse stirring, the stirring rate is about 550r / min, the alternating interval time of forward and reverse stirring is about 0.5min, and the total stirring time is about 10min; step ②. Heat the mixer to about 55°C and keep it warm, and continue stirring for about 30min to obtain a composite halogen-free flame retardant mixture;

[0127] The obtained composite halogen-free flame retardant mixture is used for standby use;

[0128] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0129] The plasticizing time is about 58 minutes to obtain a mixed rubber base;

[0130] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0131] The internal mixer was heated to about 99°C and the mixing time was about 40 minutes to obtain a mixed rubber material 1;

[0132] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0133] The mixing time is about 27 minutes, and the mixed rubber material 2 is obtained;

[0134] Step 5. Filter the mixed rubber material 2 in a filter, wherein the filter has a front layer and a rear layer of filter screens, the first layer of filter screen is about 60 meshes, and the second layer of filter screen is about 80 meshes;

[0135] The mixed rubber material 2 is filtered three times before and after in the filter to remove impurities;

[0136] Step 6. The filtered rubber material is sheeted on a calender and left to stand for about 26 hours after cooling;

[0137] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0138] The mixing time is about 30 minutes, and the mixed rubber material 3 is obtained;

[0139] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0140] The mixing time is about 30 minutes, and the mixed rubber material 4 is obtained;

[0141] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0142] Example 4

[0143] The raw material ratio of the sheath rubber system of the present invention is calculated according to the following components by weight:

[0144] 47 parts of polyurethane rubber, 24 parts of styrene-butadiene rubber, 60 parts of EPDM-graphene mixture, 27 parts of nitrile rubber, 15 parts of sodium silicate adhesive, 6 parts of hexamethylcyclotrisilazane, 8 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 15 parts of liquid silicone rubber, 1.4 parts of organic silane coupling agent, 0.8 parts of cycloalkyl rubber oil, 14 parts of nano boron nitride powder, 4 parts of granular acetylene conductive carbon black, 33 parts of composite halogen-free flame retardant system, 26 parts of reinforcing agent, 5 parts of antioxidant, 14 parts of low-temperature plasticizer, and 4 parts of vulcanization system additives.

[0145] In the above-mentioned rubber system, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0146] 75 parts of EPDM rubber, 4 parts of graphene powder, 0.5 parts of graphene dispersant, 2.5 parts of nano zinc oxide, and 12 parts of sodium silicate adhesive.

[0147] In the above-mentioned rubber system, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0148] 14 parts of DOPO intermediate, 8 parts of aluminum hydroxide, 9 parts of magnesium hydroxide, 5 parts of expandable graphite, and 14 parts of cycloalkyl rubber oil.

[0149] In the above-mentioned rubber system, the grafting rate of maleic anhydride grafted ethylene vinyl acetate copolymer is in the range of 1.5-2.0%, and the incorporation index is in the range of 3-6 g / 10 min.

[0150] The preparation method of the above-mentioned rubber system comprises the following process steps:

[0151] Step 1. Prepare an EPDM-graphene mixture, and the specific preparation method includes the following detailed process steps: Step ①. Disperse graphene powder in a sodium silicate binder; use an ultrasonic rod for ultrasonic mixing, the ultrasonic frequency is about 2750HZ, and the ultrasonic vibration time is about 24min to obtain a graphene adhesive; Step ②. Preheat an internal mixer to about 118°C; add EPDM, a graphene dispersant, nano zinc oxide and a graphene adhesive into the internal mixer; adjust the speed of the internal mixer to about 110 rpm, adjust the heating temperature of the internal mixer to about 86°C, and perform high-speed shear dispersion on the materials in the internal mixer for at least about 20min to obtain an EPDM-graphene mixture;

[0152] The obtained EPDM-graphene mixture is used for later use;

[0153] The composite halogen-free flame retardant system is prepared. The specific preparation method includes the following detailed process steps: step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite, and cycloalkyl rubber oil into a mixer; mix them in an alternating manner of forward stirring and reverse stirring, the stirring rate is about 400r / min, the alternating interval time of forward and reverse stirring is about 1.8min, and the total stirring time is about 20min; step ②. Heat the mixer to about 63°C and keep it warm, and continue stirring for about 28min to obtain a composite halogen-free flame retardant mixture;

[0154] The obtained composite halogen-free flame retardant mixture is used for standby use;

[0155] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0156] The plasticizing time is about 50 minutes to obtain a mixed rubber base;

[0157] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0158] The internal mixer was heated to about 95°C and the mixing time was about 42 minutes to obtain a mixed rubber material 1;

[0159] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0160] The mixing time is about 20 minutes to obtain the mixed rubber material 2;

[0161] Step 5. Filter the mixed rubber material 2 in a filter, wherein the filter has a front layer and a rear layer of filter screens, the first layer of filter screen is about 60 meshes, and the second layer of filter screen is about 80 meshes;

[0162] The mixed rubber material 2 is filtered twice before and after in the filter to remove impurities;

[0163] Step 6. The filtered rubber material is sheeted on a calender and left to stand for about 24 hours after cooling;

[0164] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0165] The mixing time is about 28 minutes, and the mixed rubber material 3 is obtained;

[0166] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0167] The mixing time is about 28 minutes, and the mixed rubber material 4 is obtained;

[0168] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0169] Example 5

[0170] The raw material ratio of the sheath rubber system of the present invention is calculated according to the following components by weight:

[0171] 48 parts of polyurethane rubber, 17 parts of styrene-butadiene rubber, 75 parts of EPDM-graphene mixture, 30 parts of nitrile rubber, 20 parts of sodium silicate adhesive, 5 parts of hexamethylcyclotrisilazane, 6 parts of maleic anhydride grafted ethylene vinyl acetate copolymer, 15 parts of liquid silicone rubber, 1.5 parts of organic silane coupling agent, 0.8 parts of cycloalkyl rubber oil, 15 parts of nano boron nitride powder, 2.5 parts of granular acetylene conductive carbon black, 35 parts of composite halogen-free flame retardant system, 28 parts of reinforcing agent, 6 parts of antioxidant, 15 parts of low-temperature plasticizer, and 5 parts of vulcanization system additives.

[0172] In the above-mentioned rubber system, the raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components:

[0173] 80 parts of EPDM rubber, 4 parts of graphene powder, 0.4 parts of graphene dispersant, 3 parts of nano zinc oxide, and 15 parts of sodium silicate adhesive.

[0174] In the above-mentioned rubber system, the raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components:

[0175] 15 parts of DOPO intermediate, 10 parts of aluminum hydroxide, 10 parts of magnesium hydroxide, 5 parts of expandable graphite, and 15 parts of cycloalkyl rubber oil.

[0176] In the above-mentioned rubber system, the grafting rate of maleic anhydride grafted ethylene vinyl acetate copolymer is in the range of 1.5-2.0%, and the incorporation index is in the range of 3-6 g / 10 min.

[0177] The preparation method of the above-mentioned rubber system comprises the following process steps:

[0178] Step 1. Prepare an EPDM-graphene mixture, and the specific preparation method includes the following detailed process steps: Step ①. Disperse graphene powder in sodium silicate adhesive; use an ultrasonic rod for ultrasonic mixing, the ultrasonic frequency is about 2600HZ, and the ultrasonic vibration time is about 21min, to obtain a graphene adhesive; Step ②. Preheat the internal mixer to about 120°C; add EPDM, graphene dispersant, nano zinc oxide and graphene adhesive into the internal mixer; adjust the speed of the internal mixer to about 117 rpm, adjust the heating temperature of the internal mixer to 85°C, and perform high-speed shear dispersion on the materials in the internal mixer for about 20min to obtain an EPDM-graphene mixture;

[0179] The obtained EPDM-graphene mixture is used for later use;

[0180] The composite halogen-free flame retardant system is prepared. The specific preparation method includes the following detailed process steps: step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite, and cycloalkyl rubber oil into a mixer; mix them in an alternating manner of forward stirring and reverse stirring, the stirring rate is about 600r / min, the alternating interval time of forward and reverse stirring is about 0.6min, and the total stirring time is about 20min; step ②. Heat the mixer to about 64°C and keep it warm, and continue stirring for about 120min to obtain a composite halogen-free flame retardant mixture;

[0181] The obtained composite halogen-free flame retardant mixture is used for standby use;

[0182] Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing;

[0183] The plasticizing time is about 60 minutes to obtain a mixed rubber base;

[0184] Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing;

[0185] The internal mixer was heated to about 92°C and the mixing time was about 44 minutes to obtain a mixed rubber compound 1;

[0186] Step 4. Transfer the mixed rubber material to an open mixer for mixing;

[0187] The mixing time is about 30 minutes to obtain the mixed rubber material 2;

[0188] Step 5. Filter the mixed rubber material 2 in a filter, wherein the filter has a front layer and a rear layer of filter screens, the first layer of filter screen is about 60 meshes, and the second layer of filter screen is about 80 meshes;

[0189] The mixed rubber material 2 is filtered twice before and after in the filter to remove impurities;

[0190] Step 6. The filtered rubber material is sheeted on a calender and left to stand for about 24 hours after cooling;

[0191] Step 7. Add the parked rubber material into the internal mixer for mixing;

[0192] The mixing time is about 25 minutes, and the mixed rubber material 3 is obtained;

[0193] Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing;

[0194] The mixing time is about 26 minutes, and the mixed rubber material 4 is obtained;

[0195] Step 9. Sheet the mixed rubber material 4 on a calender, cool it, and obtain a sheath rubber film for energy storage battery connecting cable.

[0196] The rubber materials prepared in the above-mentioned embodiments 1 to 5 were subjected to laboratory tests, and the performance parameters shown in the following table (ie, Table 1) were obtained.

[0197] Table 1 Performance test results of the rubber materials obtained in Examples 1 to 5

[0198]

[0199]

[0200] It can be clearly seen from the test results in the above table that the rubber compound of the present invention has excellent performance and can fully meet the ideal technical requirements for the sheath layer of the energy storage battery connection cable.

[0201] The above embodiments are only used to illustrate the present invention, but not to limit it.

[0202] Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the above embodiments or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not deviate the essence of the corresponding technical solutions from the spirit and scope of the present invention.

Claims

1. A sheath rubber material for an energy storage battery connecting cable, wherein the energy storage battery is a lead-acid battery containing battery acid; It is characterized in that The raw material ratio of the sheath rubber material is calculated according to the following weight components: Polyurethane rubber 35-50 parts, 15-25 parts of styrene-butadiene rubber, 60-80 parts of EPDM-graphene mixture, 20-30 parts of nitrile rubber, Sodium silicate adhesive 10-20 parts, 4 to 8 parts of hexamethylcyclotrisilazane, Maleic anhydride grafted ethylene vinyl acetate copolymer 5-10 parts, Liquid silicone rubber 10-15 parts, 1 to 1.5 parts of organic silane coupling agent, 0.5-1 part of naphthenic rubber oil, 10-15 parts of nano boron nitride powder, Granular acetylene conductive carbon black 2-4 parts, 25-35 parts of composite halogen-free flame retardant system, 15-30 parts of reinforcing agent, 3-6 parts of antioxidant, 10-15 parts of low temperature plasticizer, 3-5 parts of vulcanization system additives; The raw material ratio of the EPDM rubber-graphene mixture is calculated according to the following weight components: 60-80 parts of EPDM rubber, 2-4 parts of graphene powder, 0.2-0.5 parts of graphene dispersant, 1-3 parts of nano zinc oxide, 10-15 parts of sodium silicate adhesive; The raw material ratio of the composite halogen-free flame retardant system is calculated according to the following weight components: 10-15 parts of DOPO intermediate, 5-10 parts of aluminum hydroxide, 5-10 parts of magnesium hydroxide, 2-5 parts expandable graphite, 10-15 parts of cycloalkyl rubber oil; The grafting rate of the maleic anhydride grafted ethylene vinyl acetate copolymer is 1.5-2.0%, and the melt index is 3-6 g / 10 min.

2. A method for preparing the sheath rubber material for the energy storage battery connecting cable according to claim 1, It is characterized in that The preparation method comprises the following process steps: Step 1. Prepare an EPDM rubber-graphene mixture for later use; Prepare a composite halogen-free flame retardant system for standby use; Step 2. Put the polyurethane rubber, styrene-butadiene rubber, EPDM rubber-graphene mixture and nitrile rubber into an open mill for plasticizing; The plasticizing time is 50 to 60 minutes to obtain a mixed rubber base material; Step 3. Put the mixed rubber base material, sodium silicate adhesive, hexamethylcyclotrisilazane, maleic anhydride grafted ethylene vinyl acetate copolymer, liquid silicone rubber, organic silane coupling agent, cycloalkyl rubber oil, nano boron nitride powder, granular acetylene conductive carbon black, composite halogen-free flame retardant system, reinforcing agent, antioxidant, and low-temperature plasticizer into an internal mixer for mixing; The internal mixer is heated to 90-100°C and the mixing time is 40-45 minutes to obtain a mixed rubber material 1; Step 4. Transfer the mixed rubber material to an open mixer for mixing; The mixing time is 20 to 30 minutes to obtain mixed rubber material 2; Step 5. Filter the mixed rubber material 2 in a filter; Step 6. The filtered rubber material is sheeted on a calender and left to stand for at least 24 hours after cooling; Step 7. Add the stored rubber material into the internal mixer for mixing; The mixing time is 25 to 30 minutes to obtain mixed rubber material 3; Step 8. Transfer the mixed rubber material to an open mixer, add a vulcanization system additive, and continue mixing; The mixing time is 25 to 30 minutes to obtain mixed rubber material 4; Step 9. Sheet the mixed rubber material 4 on a calender and cool it to obtain a sheath rubber film for energy storage battery connecting cable.

3. The method for preparing the sheath rubber compound for the energy storage battery connecting cable according to claim 2, It is characterized in that The method for preparing the EPDM rubber-graphene mixture in step 1 specifically comprises the following process steps: Step ①. Dispersing graphene powder in sodium silicate binder; An ultrasonic rod is used for ultrasonic mixing, the ultrasonic frequency is 2500-3000 Hz, and the ultrasonic vibration time is 20-30 minutes to obtain a graphene adhesive; Step ②. Preheat the internal mixer to 115-120°C; Adding EPDM rubber, graphene dispersant, nano zinc oxide and graphene binder into an internal mixer; The rotation speed of the internal mixer is adjusted to 110-120 rpm, the heating temperature of the internal mixer is adjusted to 80-90° C., the materials in the internal mixer are subjected to high-speed shear dispersion for at least 20 minutes, and an EPDM rubber-graphene mixture is obtained.

4. The method for preparing the sheath rubber compound for energy storage battery connecting cable according to claim 2, It is characterized in that The preparation method of the composite halogen-free flame retardant system in step 1 specifically comprises the following process steps: Step ①. Put the DOPO intermediate, aluminum hydroxide, magnesium hydroxide, expandable graphite and cycloalkyl rubber oil into a mixer; Mixing is performed in an alternating manner of forward stirring and reverse stirring, the stirring rate is 400-600 r / min, the alternating interval between forward and reverse stirring is 0.5-2 min, and the total stirring time is 10-20 min; Step ②. Heat the mixer to 55-65°C and keep warm, continue stirring for 15-30 minutes to obtain a composite halogen-free flame retardant mixture.

5. The method for preparing the sheath rubber compound for energy storage battery connection cable according to claim 2, It is characterized in that The filter in step 5 has two layers of filter screens, the first layer of filter screen is 60 mesh and the second layer of filter screen is 80 mesh; The second mixed rubber material is filtered at least twice before and after in the filter.

Citation Information

Patent Citations

  • Irradiation crosslinking silicone rubber base material energy storage cable material and preparation method thereof

    CN112430367A

  • High-strength cable material and preparation method thereof

    CN107083046A

  • Cable sheath sizing material and preparation method thereof

    CN108485048A

  • Underwater cable solid filling material, preparation method and application

    CN111518253A

  • Low-smoke flame-retardant high-strength high-oil-resistance cable sheath material and preparation method thereof

    CN112500693A